DEFINITIONS OF INFORMATION: ANALYSIS OF ACADEMIC WORKS - Vasila Mamadayupova; Abrorjon Yormatov (Scholar Express Journals, 2022)
This article examines the essence of the concept of information security, opinions, approaches of scientists regarding this concept. As a result, a practical proposal is given regarding the formulation of this concept in a new form
Keywords: information security; opinion; scientists; status